SOCIAL PRACTICES OF BOURDIEU THEORY IN JAVA OPERA FILM - Teguh Tri Wahyudi; Taufiq Kurniawan; Muhammad Zaini; Inawati inawati (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2020)
This article is written based on a case study of the Javanese Opera film. A film was produced at the end of 2006 as a requiem form of disasters that occurred in Indonesian territory. The data source is based on a cut of the film scene which is approached with the social practice model according to Bourdieu's theory. The result is a picture of a woman's loyalty as a wife who is loyal to her husband. Women are strong figures, although in practice they must accept their nature. This social practice based on Javanese culture is evident in the film media, which functions as a conveyor of information and as a means of cultural transformation.Keywords: Social practice, Bordieu, film, Javanese opera, women.